Análise das metodologias do sistema das Nações Unidas de indicadores de desenvolvimento humano sustentável - Sartori, André Giovanini de Oliveira (Universidade Federal de São Carlos, 2012)
This paper analyzes the capacity that systems of indicators and synthesis-indicators; made or based on adapted methodologies developed by UN; have to operationalize the phenomenon about human and sustainable development; in the urban environment scale. The aim is to identify; systematize and analyze how the component variables of urban environment are approached by every set of indicators studied; relating the strengths and weaknesses of them for the utilization as information tools; to support decision making; within the scope of planning and urban management. The following synthesis-indicators selected are: Municipal Human Development Index (IDH-M) and Paulista Index of Social Responsibility (IPRS); the systems of indicators: Sustainable Development Index (IDS); Millennium Development Goals (ODM); GEO Cities Methodology and Habitat Agenda Indicators. The research method is based on analysis of collected indicators according to their treatment relative to the Bellagio Principles (IISD; 2000); and also regarding to the common variables of planning and management of urban environment; which are set as sanitation; habitation; environment; mobility; security and education. The results show that synthesis indicators and systems indicators studied are both not appropriate; rather in relation to meeting Bellagio Principles; than regarding the coverage of common variables to planning and management of urban environment. The synthesis indicators show their qualities to effective communication and guiding vision and goals; whereas systems of indicators show advantages on assessment capability of the system itself. Regarding to the strengths and weaknesses of the set of indicators studied for the utilization in urban planning; the utilization of these indicators; as information tools in decision making process; tends to be done in an indirect way. As a final conclusion of this paper; outstands that the utilization of indicators tends to be considered as a way to help to understand our daily routine. Nowadays; the systems of indicators and synthesis indicators available do not meet ideal conditions to analyze the urban environment in a holistic perspective; because there are weaknesses and gaps that harm its operation.
Keywords: Engenharia urbana; Desenvolvimento Sustentável; Indicadores; Meio Urbano; Sustainable Development; Indicators; Urban Environment; ENGENHARIAS::ENGENHARIA CIVIL